Bone Quantification Around Chitosan-Coated Titanium Dental Implants: A Preliminary Study by Micro-CT Analysis in Jaw of a Canine Model - López-Valverde, Nansi; López-Valverde, Antonio; Cortés, Marta Paz; Rodríguez, Cinthia; Macedo De Sousa, Bruno; Aragoneses, Juan Manuel (Frontiers in Bioengineering and Biotechnology, 2022)
Surface treatments of Ti in the dental implant industry are performed with the aim of in-creasing its bioactivity and osseointegration capacity. Chitosan (Cht) is a polysaccharide that has been proposed as a promising biomaterial in tissue engineering and bone regeneration, due to its ability to stimulate the recruitment and adhesion of osteogenic progenitor cells. The aim of our preliminary study was to evaluate, by micro-computed tomography (micro-CT), the osseointegration and bone formation around Cht-coated implants and to compare them with conventional surface-etched implants (SLA type). Four im-plants (8.5 mm length x 3.5 mm Ø) per hemiarch, were inserted into the jaws of five dogs, divided into two groups: chitosan-coated implant group (ChtG) and control group (CG). Twelve weeks after surgery, euthanasia was performed, and sectioned bone blocks were obtained and scanned by micro-CT and two bone parameters were measured: bone in contact with the implant surface (BCIS) and peri-implant bone area (PIBA). For BCIS and PIBA statistically significant values were obtained for the ChtG group with respect to CG (p=0.005; p=0.014 and p<0.001 and p=0.002, respectively). The results, despite the limitations, demonstrated the usefulness of chitosan coatings. However, studies with larger sample sizes and adequate experimental models would be necessary to confirm the results.